Strategi Pemasaran Digital Syariah dalam Meningkatkan Preferensi Pembelian Ulang Konsumen - Putri Dayana Putri Dayana; Sukamto; Aslikhah (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to describe the Islamic digital marketing strategy applied by Abu 'Alwi Perfume Store in Sukorejo to enhance consumer repurchase preference. In the digital economy era, the integration of Islamic values such as shiddiq (honest), amanah (trustworthy), fathanah (intelligent), and tabligh (communicative) becomes key in building customer trust on digital platforms. The research employs a descriptive qualitative method with data collection techniques including observation, in-depth interviews, and documentation. The findings reveal that Abu 'Alwi Perfume Store successfully utilizes social media platforms such as TikTok, Instagram, Facebook, and WhatsApp to build an honest and transparent brand image. This strategy encompasses educational content, customer testimonials, and responsive services that reflect Islamic values. Consistency between digital promotions and actual product quality emerges as the primary factor driving customer loyalty and repurchase preference. Through this approach, the store not only increases sales but also strengthens emotional relationships and customer trust, thereby creating sustainable competitive advantage in an increasingly competitive digital marketplace. This research contributes to the development of a digital-based Islamic marketing model that remains relevant to contemporary consumer needs